Dactinomycin in acute myeloid leukemia with NPM1 mutations. (25th May 2020) - Beziat, Guillaume; Tavitian, Suzanne; Bertoli, Sarah; Huguet, Françoise; Largeaud, Laetitia; Luquet, Isabelle; Vergez, François; Rieu, Jean‐Baptiste; Bories, Pierre; Delabesse, Eric; Récher, Christian
Abstract: Objectives: Complete responses have been observed in NPM1 ‐mutated AML patients with dactinomycin, a nucleolar stress‐inducing drug. Here, we report a single‐center experience of compassionate use of dactinomycin in untreated or relapsed/ refractory NPM1 ‐mutated AML. Methods: From September 2015 to February 2019, 26 adult patients with NPM1 ‐mutated AML received dactinomycin in different situations: front‐line treatment in 4 unfit patients (16%); morphologic (n = 16, 62%), molecular relapses (n = 4, 16%), refractory disease (n = 1, 13%), or postremission therapy in second complete response (n = 1, 13%). Results: Median age was 62.5 years. Median number of dactinomycin cycle was 1 (1‐8), and 7 patients (27%) received more than 3 cycles. Three out of 17 patients (18%) in morphologic relapse or refractory to chemotherapy achieved complete remission after the first cycle of dactinomycin. None of the 4 patients unfit for intensive chemotherapy responded to dactinomycin as front‐line therapy. Grade 3‐4 adverse events were thrombocytopenia (n = 11, 42%), neutropenia (n = 11, 42%), GI toxicity (n = 6, 23%), mucositis (n = 5, 19%), lung infection (n = 5, 19%), and skin rash (n = 2, 7.6%). Conclusions: Dactinomycin is an inexpensive and easily available drug that may induce significant responses in few AML patients with NPM1 mutations with an acceptable safety profile.